Ecology, the pace‐of‐life, epistatic selection and the maintenance of genetic variation in life‐history genes - Göran Arnqvist; Locke Rowe (Molecular Ecology, 2023)
Evolutionary genetics has long struggled with understanding how functional genes under selection remain polymorphic in natural populations. Taking as a starting point that natural selection is ultimately a manifestation of ecological processes, we spotlight an underemphasized and potentially ubiquitous ecological effect that may have fundamental effects on the maintenance of genetic variation. Negative frequency dependency is a well‐established emergent property of density dependence in ecology, because the relative profitability of different modes of exploiting or utilizing limiting resources tends to be inversely proportional to their frequency in a population. We suggest that this may often generate negative frequency‐dependent selection (NFDS) on major effect loci that affect rate‐dependent physiological processes, such as metabolic rate, that are phenotypically manifested as polymorphism in pace‐of‐life syndromes. When such a locus under NFDS shows stable intermediate frequency polymorphism, this should generate epistatic selection potentially involving large numbers of loci with more minor effects on life‐history (LH) traits. When alternative alleles at such loci show sign epistasis with a major effect locus, this associative NFDS will promote the maintenance of polygenic variation in LH genes. We provide examples of the kind of major effect loci that could be involved and suggest empirical avenues that may better inform us on the importance and reach of this process.

The role of ecology, neutral processes and antagonistic coevolution in an apparent sexual arms race - Jennifer C. Perry; Colin J. Garroway; Locke Rowe (Ecology Letters, 2017)
Some of the strongest examples of a sexual ‘arms race’ come from observations of correlated evolution in sexually antagonistic traits among populations. However, it remains unclear whether these cases truly represent sexually antagonistic coevolution; alternatively, ecological or neutral processes might also drive correlated evolution. To investigate these alternatives, we evaluated the contributions of intersex genetic correlations, ecological context, neutral genetic divergence and sexual coevolution in the correlated evolution of antagonistic traits among populations of Gerris incognitus water striders. We could not detect intersex genetic correlations for these sexually antagonistic traits. Ecological variation was related to population variation in the key female antagonistic trait (spine length, a defence against males), as well as body size. Nevertheless, population covariation between sexually antagonistic traits remained substantial and significant even after accounting for all of these processes. Our results therefore provide strong evidence for a contemporary sexual arms race.

Female choice and the relatedness of mates in the guppy (Poecilia reticulata) - Trevor E. Pitcher; F. Helen Rodd; Locke Rowe (Genetica, 2008)

Resource limitation, predation risk and compensatory growth in a damselfly - Caitlin Dmitriew; Locke Rowe (Oecologia, 2005)

Community responses to experimental food depletion: resource tracking by stream invertebrates - Locke Rowe; John S. Richardson (Oecologia, 2001)